0.3分之1-0.5x减0.3分之0.2x-1=0.02分之0.3x.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 21:10:10
0.3分之1-0.5x减0.3分之0.2x-1=0.02分之0.3x.0.3分之1-0.5x减0.3分之0.2x-1=0.02分之0.3x.0.3分之1-0.5x减0.3分之0.2x-1=0.02分之
0.3分之1-0.5x减0.3分之0.2x-1=0.02分之0.3x.
0.3分之1-0.5x减0.3分之0.2x-1=0.02分之0.3x.
0.3分之1-0.5x减0.3分之0.2x-1=0.02分之0.3x.
0.3分之1-0.5x减0.3分之0.2x-1=0.02分之0.3x 两边乘0.3
1-0.5x-0.2x+1=4.5x
4.5x+0.5x+0.2x=2
5.2x=2
x=5/13
如果本题有什么不明白可以追问,
0.3分之1-0.5x减0.3分之0.2x-1=0.02分之0.3x.
0.2分之0.3x+0.5减3分之2x=负3分之
0.3分之x=1+0.2分之1.2-0.3x
0.2分之x-0.01分之0.3x=1
0.7分之x-0.3分之0.7-0.2x=1
0.7分之x-0.3分之0.7-0.2x=1
0.5分之2X-1=0.3分之X+1
0.3分之x-1-0.5分之x+2=12
0.3分之x-1-0.5分之x+2=-4
0.3分之(1-0.5x)-(3分之2)x=0.02分之(0.3x)+1
解方程:0.2分之x-1=0.3分之1.7-2x+0.6分之0.5+2x
解方程:0.2分之0.3x+0.5-0.03分之0.02-0.05x=3分之2x+1
0.3分之3x-1=0.6分之4-x +0.2分之3x+5
六分之5X-1=3分之5 0.5分之X=0.3分之X-1.8
0.1分之(1+x)减0.2分之(0.4x-0.5)=2分之1
0.3分之0.5x 0.7 0.2分之0.3x+0.1=1
0.3分之0.5x-0.7-0.2分之0.3x+0.1=1,
0.2减(0.2分之X-1)=0.3分之1加x